2021
DOI: 10.1371/journal.pone.0261499
|View full text |Cite
|
Sign up to set email alerts
|

Validation of color Doppler ultrasound and computed tomography in the radiologic assessment of non-malignant acute splanchnic vein thrombosis

Abstract: Introduction International guidelines propose color Doppler ultrasound (CDUS) and contrast-enhanced computed tomography (CT) as primary imaging techniques in the diagnosis of acute splanchnic vein thrombosis. However, their reliability in this context is poorly investigated. Therefore, the aim of our study was to validate CDUS and CT in the radiologic assessment of acute splanchnic vein thrombosis, using direct transjugular spleno-portography as gold standard. Materials and methods 49 patients with non-malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…On admission, our patient’s routine investigations showed a high white blood cell count and high hemoglobin and D-dimer levels. Additionally, she was a young woman taking oral contraceptives, who presented with acute severe abdominal pain not consistent with her physical examination findings according to the previous literature[ 13 , 20 ]. Accordingly, we suspected the possibility of AMI induced by MVT, and she was finally diagnosed with AMI induced by PMSVT.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On admission, our patient’s routine investigations showed a high white blood cell count and high hemoglobin and D-dimer levels. Additionally, she was a young woman taking oral contraceptives, who presented with acute severe abdominal pain not consistent with her physical examination findings according to the previous literature[ 13 , 20 ]. Accordingly, we suspected the possibility of AMI induced by MVT, and she was finally diagnosed with AMI induced by PMSVT.…”
Section: Discussionmentioning
confidence: 90%
“…The EASL Clinical Practice Guidelines[ 11 ] and AASLD Practice Guidelines[ 12 ] propose color Doppler sonography (CDUS) and CECT as the primary imaging techniques for diagnosing acute splanchnic vein thrombosis. Sturm et al [ 13 ] demonstrated that CDUS and CECT are equally reliable in assessing the grade and extent of acute splanchnic vein thrombosis[ 13 ]. The diagnostic sensitivity and specificity of CDUS in detecting PV thrombosis (PVT) vary from 66% to 100%[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…DVT is characterized by occult onset and low diagnostic rate using conventional Doppler ultrasound, resulting in the lack of effective control of the occurrence of DVT. 4 Meanwhile, venography is costly and time-consuming, despite high diagnostic accuracy. 5 Consequently, it is important to determine a more convenient and efficient diagnostic mode.…”
Section: Introductionmentioning
confidence: 99%
“…DVT is characterized by occult onset and low diagnostic rate using conventional Doppler ultrasound, resulting in the lack of effective control of the occurrence of DVT. 4 …”
Section: Introductionmentioning
confidence: 99%
“…However, radiation exposure and expensive price restrict the application of the diagnosis [ 9 ]. Featuring with high sensitivity and accuracy, color Doppler ultrasound has been applied to the diagnosis of DVT [ 10 , 11 ]. However, the guiding value for clinical doctors to prevent thrombosis is limited.…”
Section: Introductionmentioning
confidence: 99%